2022
DOI: 10.3390/cells11213359
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Cytotoxic T Cells and Dysfunctional CD8 T Cells in Severe COVID-19 Patients

Abstract: COVID-19, the infectious disease caused by SARS-CoV-2, has spread on a pandemic scale. The viral infection can evolve asymptomatically or can generate severe symptoms, influenced by the presence of comorbidities. Lymphopenia based on the severity of symptoms in patients affected with COVID-19 is frequent. However, the profiles of CD4+ and CD8+ T cells regarding cytotoxicity and antiviral factor expression have not yet been completely elucidated in acute SARS-CoV-2 infections. The purpose of this study was to e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…It has been demonstrated earlier that patients with COVID-19 shifted towards a cytotoxic phenotype in the T cell compartment, as indicated by high degranulation capacity (granzyme B and perforin levels) compared to healthy controls [2]. However, another study found an abnormal CD8 + T cells response characterized by reduced perforin levels in patients with severe COVID-19 [1]. In our study, intracellular levels of granzyme B in CD56 + T cells were higher in the ICU patients compared to HD, while CD56 − T cells in the CCP group had reduced granzyme B + cell content compared to the MS group (Figure 3a).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been demonstrated earlier that patients with COVID-19 shifted towards a cytotoxic phenotype in the T cell compartment, as indicated by high degranulation capacity (granzyme B and perforin levels) compared to healthy controls [2]. However, another study found an abnormal CD8 + T cells response characterized by reduced perforin levels in patients with severe COVID-19 [1]. In our study, intracellular levels of granzyme B in CD56 + T cells were higher in the ICU patients compared to HD, while CD56 − T cells in the CCP group had reduced granzyme B + cell content compared to the MS group (Figure 3a).…”
Section: Discussionmentioning
confidence: 93%
“…Coronavirus Disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) leads to complex immune dysregulation and affects different components of the antiviral cellular immunity. In particular, T cell immune response, which plays an essential role in infection control, may vary in patients with mild, moderate, and severe COVID-19 [1,2]. The question about the predictive significance of different T cell markers of activation, differentiation, or exhaustion in COVID-19 remains relevant.…”
Section: Introductionmentioning
confidence: 99%
“…As of writing this report, we had enrolled 66 COVID-19 admission patients including 17 in the M/M group, 24 in the S group, and 25 in the C group. The median disease duration before admission was 11 days [ 10 , 13 ] in the M/M group, 10 days [ 7 , 14 ] in the S group and 9 days [ 7 , 10 ] in the C group. The median age of patients in the three COVID-19 groups was 70 years [57, 83], 77 years [68, 82], and 74 years [67, 80], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this cohort, the peripheral neutrophilia along with lymphopenia was more pronounced in patients with an S/C condition, which had been indicated as a predictor of the severity of COVID-19 due to the infiltration of neutrophils in the histopathological lung lesion [ 15 ]. Based on our observation, we captured the rapid restoration of peripheral lymphocyte counts in the M/M group rather than the S/C group ( Figure 3 ), as previous data indicated a slow restoration capacity of lymphocytes in most severe cases [ 13 ]. Although the detailed mechanism of the rapid reduction and slow restoration of lymphocyte counts is still unclear, it reminded clinicians to alert to S/C COVID-19 with potentially worse outcomes, as did in SARS [ 11 ].…”
Section: Discussionmentioning
confidence: 95%
“…SARS‐CoV‐2 spike glycoprotein was capable of inducing a rapid membrane fusion to produce syncytium, which was seen to readily internalise multiple lines of lymphocytes to form typical cell‐in‐cell structures, remarkably leading to the death of internalized cells 21 . Interestingly, prolonged hospitalizations with COVID resulted in no overt recovery of B or CD4+ T cell lymphocytes 22 . Whereas in SARS‐CoV1, CD8+ T lymphocytes normalised after 3 months of symptom onset, and CD4+ lymphocytes were still decreased in almost half of people after a year; total lymphocytes were still decreased after 16 weeks.…”
Section: Mechanism Of Cell Death Following Infection Of Macrophages L...mentioning
confidence: 99%